Evaluation of water-in-diesel emulsion fuel blended with metal additives in a diesel engine / J. B. Fletcher ... [et al.] - Fletcher, J. B.; Ithnin, A. M.; Yahya, W. J.; Kadir, H. A.; Ramlan, A. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Diesel engines are highly preferred in transportation and industrial application as they are more efficient and durable in comparison to gasoline engine. However, they produce high Nitrogen Oxides (NOx) and Particulate Matter (PM) emissions which contributed to major source of air pollution in the environment. Water-in-diesel (W/D) emulsion fuels are being introduced as alternative fuels to reduce NOx and PM emissions respectively. But, the utilization of W/D emulsion fuels contributed to higher CO emissions. Supplementing metal additives into the fuel is the alternative way to reduce the CO emissions and improve performance. The test were carried out to evaluate the effect of organic based manganese blended with the emulsion fuel to the engine fuel consumption and exhaust emissions. Three different organic manganese (100ppm, 150ppm, and 200ppm) were blended with the emulsion fuel (E10: 89%, water: 10%, surfactant: 1%) and labelled as E10Mn100, E10Mn150, and E10Mn200. For performance and emissions tests, the engine were set to run at 3500 rpm for every 0 kW, 1 kW, 3 kW, and 5 kW. E10Mn200 which showed the maximum decrease of fuel consumption (FC) and the highest exhaust gas temperature at 1.53% and 62.86% respectively in comparison with E10. Whereas, E10Mn150 displayed the highest reduction of CO at 14.67%, showing maximum rate increase at 28.24% in NOx emissions, and minimum hydrocarbon (HC) emissions in comparison with E10. NOx emissions start to reduce after addition of 200ppm additives. Organic-based manganese act as a catalyst that promotes improvement of the emulsion fuel performance and reduce the harmful emissions discharged.